2016
DOI: 10.1007/s11356-016-8113-z
|View full text |Cite
|
Sign up to set email alerts
|

Pollution characteristics and ecological risk of heavy metals in ballast tank sediment

Abstract: This study was conducted to illustrate the contents and potential ecological risk of heavy metals in ballast tank sediment. Ballast sediment samples were collected from six ships during their stay in shipyard, and the heavy metals were determined by inductive coupled plasma emission spectrometer. Results showed that high concentrations of heavy metals were detected in all six sediment samples following the order: Zn > Cu > Pb > Cr > As > Cd > Hg. The geoaccumulation index explained the average pollution degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A study by Nosrati-Ghods et al [42] found that values of Cr (2.1 mg L −1 ) and Ni (0.029 mg L −1 ) in ballast water were higher than in seawater. Research by Feng et al [43] also found increased contents of Zn, Cu, Pb, Cr, and As in ballast tank sediments. High contents of Cu and Cr, and the highest value of Pb were also recorded in Dapeng cove (S12) with the presence of cage aquaculture.…”
Section: Mean Concentrations and Comparisonsmentioning
confidence: 86%
See 1 more Smart Citation
“…A study by Nosrati-Ghods et al [42] found that values of Cr (2.1 mg L −1 ) and Ni (0.029 mg L −1 ) in ballast water were higher than in seawater. Research by Feng et al [43] also found increased contents of Zn, Cu, Pb, Cr, and As in ballast tank sediments. High contents of Cu and Cr, and the highest value of Pb were also recorded in Dapeng cove (S12) with the presence of cage aquaculture.…”
Section: Mean Concentrations and Comparisonsmentioning
confidence: 86%
“…The Sediment Quality Guidelines (SQGs) of China [43] are commonly used to assess the sediment quality in China. Based on Cu, Pb, Zn, Cr, and Cd contents, sediment quality is classified into three functional classes: Class I (sediment quality suitable for nature reserve, mariculture, and etc.…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
“…In the laboratory, samples were allowed to dry naturally at the ambient temperature. Before screening, the sediment samples were subjected to disaggregation and sorted into different particle sizes using a stainless-steel mesh (Feng et al, 2017). Samples were grounded to a fine powder using an electric agate mortar for less than 20 minutes, with around ten grams of each sample.…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Marine sediments accumulate in ship ballast compartments together with corrosion products from the machinery used to manage water intake and output. Collectively, these solid phases form a ballast tank sediment or sludge [1,5,8,9]. The entrainment and accumulation of marine sediment in ballast tanks is common, particularly when a vessel takes on ballast water in relatively shallow areas [5,10].…”
Section: Introductionmentioning
confidence: 99%